Designing the Cashier’s Standard Operating Procedures (SOP) for Fashion Retail Business - Henny Wirianata; Annastasha Geraldine; Cordelia Stella Chandra (Journal of Innovation and Community Engagement, 2026)
A Standard Operating Procedure (SOP) is a guideline that explains how to perform a task. SOPs can help companies prevent manipulation or fraud because each activity in a business process explains the parties involved, the transaction evidence and documentation involved, and the parties who authorize it. This community service activity was carried out in the form of mentoring for SOP preparation, which took place from August to September 2025 at PT EGP. PT EGP is a trading company whose primary business process is fashion retail. The implementation of this activity goes through five stages which include planning stage, system analysis stage, system design stage, system trial stage, and system implementation stage. This activity was carried out with conducting direct and open observations using questionnaires, interviews with owners and employees, and documenting all information and explanations obtained for each activity in the partner's business process. The resulting SOP is limited to SOP for cashiers consisting of four SOPs, namely the SOP when opening the cashier, the SOP during sales transactions, the SOP after transactions or during operations, and the SOP when closing the cashier. The cashier SOP aims to prevent and avoid manipulation and misuse of company assets by cashiers and employees responsible for sales. It is hoped that partners can implement the SOPs that have been created consistently and become a monitoring tool for owners.